2017
DOI: 10.1155/2017/4870671
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Liquid-Liquid Extraction, Solid Phase Extraction, and Headspace Technique for Determination of Some Volatile Water-Soluble Compounds of Rose Aromatic Water

Abstract: Steam distillation is used to isolate scent of rose flowers. Rose aromatic water is commonly used in European cuisine and aromatherapy besides its use in cosmetic industry for its lovely scent. In this study, three different sampling techniques, liquid-liquid extraction (LLE), headspace technique (HS), and solid phase extraction (SPE), were compared for the analysis of volatile water-soluble compounds in commercial rose aromatic water. Some volatile water-soluble compounds of rose aromatic water were also anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…This result was similar to those of previous studies [3,6,8] and consistent with the type of solvent used. In the present study, followed by the methanol chloroform extract, which agreed with earlier reports [51,52]. To date, our study was the first investigation to quantify eugenol from P. sarmentosum leaves using the liquid chromatographic principle.…”
Section: Hplc Methods Validationsupporting
confidence: 92%
“…This result was similar to those of previous studies [3,6,8] and consistent with the type of solvent used. In the present study, followed by the methanol chloroform extract, which agreed with earlier reports [51,52]. To date, our study was the first investigation to quantify eugenol from P. sarmentosum leaves using the liquid chromatographic principle.…”
Section: Hplc Methods Validationsupporting
confidence: 92%
“…Generally, the selection of a two‐phase solvent system is based on the polarity of components in plant extracts. For example, Canbay (2017) used chloroform, dichloromethane, n‐hexane, and ethyl acetate to obtain target compounds (focusing on volatile compounds) from rose aromatic water. The results showed that n‐hexane was the least suitable liquid–liquid extraction (LLE) solvent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the components of the kuromoji hydrosol (aromatic distilled water), obtained as a by-product when refining the essential oil, are unknown. When distilling plants to extract essential oils used in aromatherapy, hydrosols are obtained from the distillation kiln [ 3 , 4 ]. Essential oils and hydrosols are similar in flavor/scent and properties because they are extracted from the same plant.…”
Section: Introductionmentioning
confidence: 99%